Vanadium microalloying for ultra-high strength steel sheet treated by hot-dip metallising. Issue 4 (4th March 2017) - Hutchinson, B.; Martin, D.; Karlsson, O.; Lindberg, F.; Thoors, H.; Marceau, R. K.W.; Taylor, A. S.
Abstract : Ultra-high strength steel sheets have been subjected to heat treatments that simulate the thermal cycles in hot-dip galvanising and galvannealing processes and evaluated with respect to their resulting mechanical properties and microstructures. The steels contained suitable contents of carbon (∼0.2%), manganese (1.2%) and chromium (0.4%) to ensure that they could be fully transformed to martensite after austenitisation followed by rapid cooling in a continuous annealing line, prior to galvanising. Different contents of vanadium (0–0.1%) and nitrogen (0.002–0.012%) were used to investigate the possible role of these microalloying elements on the strength of the tempered martensite. Vanadium, especially when in combination with a raised nitrogen content, helps to resist the effect of tempering so that a larger proportion of the initial strengthening is preserved after the galvanising cycle, giving tensile strength levels exceeding 1000 MPa. Different deoxidation practices using aluminium or silicon have also been included. These showed similar strength levels at corresponding carbon contents but the bendability of the Si-killed steel sheet was considerably superior. Microstructural examinations have been made on the annealed steels but the reason for the beneficial effect of vanadium is still not fully explained. It is concluded that microalloying with vanadium is a very promising approach in the development of corrosion-resistant ultra-high strength steel sheet products.